Augmenting comprehension of geological relationships by integrating 3D laser scanned hand samples within a GIS environment. (June 2017) - Harvey, A.S.; Fotopoulos, G.; Hall, B.; Amolins, K.
Abstract: Geological observations can be made on multiple scales, including micro- (e.g. thin section), meso- (e.g. hand-sized to outcrop) and macro- (e.g. outcrop and larger) scales. Types of meso-scale samples include, but are not limited to, rocks (including drill cores), minerals, and fossils. The spatial relationship among samples paired with physical (e.g. granulometric composition, density, roughness) and chemical (e.g. mineralogical and isotopic composition) properties can aid in interpreting geological settings, such as paleo-environmental and formational conditions as well as geomorphological history. Field samples are collected along traverses in the area of interest based on characteristic representativeness of a region, predetermined rate of sampling, and/or uniqueness. The location of a sample can provide relative context in seeking out additional key samples. Beyond labelling and recording of geospatial coordinates for samples, further analysis of physical and chemical properties may be conducted in the field and laboratory. The main motivation for this paper is to present a workflow for the digital preservation of samples (via 3D laser scanning) paired with the development of cyber infrastructure, which offers geoscientists and engineers the opportunity to access an increasingly diverse worldwide collection of digital Earth materials. This paper describes a Web-based graphical user interface developed using Web AppBuilder for ArcGIS for digitized meso-scale 3D scans of geological samples to be viewed alongside the macro-scale environment. Over 100 samples of virtual rocks, minerals and fossils populate the developed geological database and are linked explicitly with their associated attributes, characteristic properties, and location. Applications of this new Web-based geological visualization paradigm in the geosciences demonstrate the utility of such a tool in an age of increasing global data sharing. Highlights: A database of virtual geological samples is populated via 3D desktop laser scanning. 3D visualization widget for meso-scale samples built for Web-based ArcGIS. Blending widget for geophysical data built to provide geological context. Geovisualization of virtual samples now possible for Web-based ArcGIS platform.